The role of interleukin-10 in normal and aberrant late lung development - Lignelli, Ettore; Justus Liebig University Giessen (My University, 2021)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease characterized by stunted lung development, simplification of alveoli and chronic inflammation. The anti-inflammatory cytokine interleukin (IL)-10, considered the keystone of anti-inflammatory immunomodulation, has been documented to be significantly downregulated in the hyperoxia (85% O2)-based murine model of BPD, suggesting administration of this cytokine as a potential therapeutic modality. Daily exogenous administration of IL-10 did not impact the lung architecture of mice exposed to 21% O2 (normoxia) or hyperoxia; furthermore, no alterations were observed in global IL-10 knockout mice exposed to either normoxia or hyperoxia. Refining the dosage by administering IL-10 solely on the first postnatal day (P) 1 induced an aggravation of the septal thickening which is one of the hallmarks of BPD, while having no observable effect in mice exposed to normoxia. No changes were also observed in mice treated with IL-10 at P3, regardless of the oxygen concentrations. Immunohistochemistry imaging revealed an increase in the abundance of fibroblasts in the septa of IL-10 treated mice exposed to hyperoxia. Flow cytometric analysis of whole lung homogenates isolated from IL-10-treated mice revealed that treatment with IL-10 rescues the eosinophilic environment associated with the chronic inflammatory component of BPD while significantly altering the composition of the T cell compartment of the immune response by raising the absolute T cell counts when administered at P1, but not at P3. A deeper analysis of T cell subsets revealed that IL-10 administration raises CD4+ cell count in mice treated at P1, while no impact was observed in mice treated at P3. The CD8+ cell count was reduced in mice exposed to normoxia and treated with IL-10 both at P1 and at P3, while CD4+ CD25+ cell count dropped in mice exposed to both normoxia and hyperoxia. An analysis conducted on whole lungs transcriptomes of mice exposed to hyperoxia and treated with IL-10 at P1 reported a switch from a strong anti-inflammatory profile observed at P2 to a profile more oriented towards the epithelial-mesenchymal transition at P3. To date, this is the first study providing detailed insights into the potential of IL-10 as a therapeutic to be employed in the treatment of BPD. These data delineate a clear picture of IL-10 as a complex, multi-layered molecule whose harnessing for translational purposes, although promising, constitutes a delicate challenge.
Keywords: BPD; Lung; Prematurity; ddc:570; ddc:610